A wide temporal window for conjunctival papillae development ensures the formation of a complete sclerotic ring. Issue 5 (2nd March 2017) - Jourdeuil, Karyn; Franz‐Odendaal, Tamara Anne
Abstract : Background : The conjunctival papillae are epithelial thickenings of the conjunctiva that are required for the induction of underlying bones (the scleral ossicles). These transient papillae develop and become inductively active over an extended temporal period (HH 30–36, 6.5–10 dpf). While their inductive capacity was discovered in the mid‐1900s, little is known about their development.Results : Through a series of timed surgical ablations followed by in situ hybridization for Bmp2, we show that the ring of conjunctival papillae is not altered if the conjunctival epithelium is ablated either prior to or shortly after papillae induction (i.e., HH 29–30, 6.5–7 dpf). A conjunctival papilla ablated at or prior to HH 34 (8 dpf), when the complete ring is present, regenerates and quickly becomes inductively active, inducing an underlying scleral condensation with only a slight delay. This regenerative capacity extends until HH 35.5, a full 36 hours beyond the normal timeline of papillae induction. As such, the period of epithelial competency for papilla induction is longer than previously identified.Conclusions : Papilla regeneration is a mechanism that ensures the formation of a complete sclerotic ring and provides another level of redundancy for the induction of a complete sclerotic ring during the normal inductive period. Developmental Dynamics 246:381–391, 2017 . © 2017 Wiley Periodicals, Inc. Key Findings: Ablated conjunctival papillae regenerate and mature quickly to induce underlying ossicles. The conjunctival epithelium is competent to respond to a mesenchymal signal until HH 35.5, one and a half days beyond the normal timeline of papillae induction. The mesenchymal signal for papillae induction is not present after HH 36. The capacity for papillae regeneration provides developmental redundancy in the ossicle system.